2002
DOI: 10.1152/ajpregu.00122.2002
|View full text |Cite
|
Sign up to set email alerts
|

Are developing β-adrenoceptors able to desensitize? Acute and chronic effects of β-agonists in neonatal heart and liver

Abstract: During fetal and neonatal development, β-adrenergic receptors (β-ARs) appear to be resistant to desensitization by β-agonist drugs. To determine the mechanisms underlying the regulatory differences between adults and neonates, we administered isoproterenol, a mixed β1/β2-AR agonist, and terbutaline, a β2-selective agonist. Effects were examined in the ensuing 4 h after a single injection, or after the last of four daily injections. We prepared cell membranes from heart (predominantly β1-ARs) and liver (predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…Differentiated, tissue-specific ␤AR regulation has previously been demonstrated and ascribed to receptor concentration, receptor subtype ratio, adenylyl cyclase isoform expression, and G protein expression (4). With our present data, we cannot discriminate which of the above factors is responsible for the increased ␤AR-mediated relaxation.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Differentiated, tissue-specific ␤AR regulation has previously been demonstrated and ascribed to receptor concentration, receptor subtype ratio, adenylyl cyclase isoform expression, and G protein expression (4). With our present data, we cannot discriminate which of the above factors is responsible for the increased ␤AR-mediated relaxation.…”
Section: Discussioncontrasting
confidence: 48%
“…Although high levels of circulating catecholamines are known to desensitize and downregulate ␤-adrenergic receptors in adult cardiac tissue, we and others have previously shown that embryonic hypoxia sensitizes ␤ARs rather than desensitizes them. The stimulatory effect of catecholamines on the heart is thereby maintained (4,24).…”
Section: Discussionmentioning
confidence: 99%
“…The same dosing regimen has been used by us and other investigators. For example, Auman et al (3) showed that the same dosing regimen for Iso activates basal adenylyl cyclase activities, measured 1-4 h after treatment, in neonatal and adult hearts. There is no homologous or heterologous desensitization of ␤-AR-mediated responses in neonatal heart and only a slight but not significant increase in homologous desensitization 1 h after Iso injection in adult hearts.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of PTEN were, however, not affected by the same treatment, suggesting a direct action of acute ␤-AR stimulation on PI3K signaling in postnatal hearts. During development, ␤-AR stimulation-induced receptor desensitization or downregulation is not present until 2 wk of age (3,44). The absence of ␤-AR desensitization in early development may be physiologically critical, as ␤-AR signaling is required for maintaining proper homeostasis and growth of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using heart, lung, brown fat, and liver suggest that immature, developing tissue is resistant to desensitization by chronic ␤-agonist exposure (3,4,9,29,36). These observations indicate that the downregulation and desensitization responses may not be inherent but are acquired during development.…”
mentioning
confidence: 99%